The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00415-010-5453-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuating cognition and different cognitive and behavioural profiles in Parkinson’s disease with dementia: comparison of dementia with Lewy bodies and Alzheimer’s disease

Abstract: To examine the occurrence of fluctuating cognition (FC) in a group of patients with Parkinson's disease with dementia (PDD), and to determine whether the presence of FC in PDD is associated with a pattern of cognitive and behavioural disturbances similar to the one shown by patients affected by dementia with Lewy bodies (DLB), a cluster analysis was carried out on the scores obtained by 27 PDD patients on the Clinician Assessment of Fluctuation Scale (CAF). The analysis separated the PDD patients into two subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 26 publications
4
35
2
Order By: Relevance
“…Demonstration of a significant amyloid pathology in [11C] Pittsburgh compound B positron-emission tomography might explain why the level of deterioration in memory and executive functions is higher in DLB than in PDD. A very recent study found that a subgroup of PDD patients not experiencing cognitive fluctuations showed significantly less attentional, executive, and memory deficits compared to those with DLB and PDD experiencing cognitive fluctuations 31. The differences in cognitive profiles between DLB and PDD in our data may be influenced by the discrepancy of distribution in the two subgroups of PDD.…”
Section: Discussioncontrasting
confidence: 55%
“…Demonstration of a significant amyloid pathology in [11C] Pittsburgh compound B positron-emission tomography might explain why the level of deterioration in memory and executive functions is higher in DLB than in PDD. A very recent study found that a subgroup of PDD patients not experiencing cognitive fluctuations showed significantly less attentional, executive, and memory deficits compared to those with DLB and PDD experiencing cognitive fluctuations 31. The differences in cognitive profiles between DLB and PDD in our data may be influenced by the discrepancy of distribution in the two subgroups of PDD.…”
Section: Discussioncontrasting
confidence: 55%
“…Given the impact of CFs on a range of cognitive functions and relationship between cognition and ADLs, it is not surprising that CFs were significantly associated with ADLs. However, both CFs and SIB total score contributed independently to the level of impairment in ADLs in our study, indicating there is an independent relationship between CFs and ADLs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated memory deficits in PDD (Higginson et al, 2005; Kuzis et al, 1999; Noe et al, 2004; Owen et al, 1993b; Varanese et al, 2010). The impairment is most evident for visual-spatial memory tasks (Noe et al, 2004; Owen et al, 1993b).…”
Section: Discussionmentioning
confidence: 99%